Strategies and policies in digital convergence - Park, Sangin, 1965- (Hershey : Idea Group Reference)
"This book addresses and positions the issues in business strategy and public policy rising from digital convergence, especially in the areas of mobile communications, broadband networks, and digital multimedia broadcast services. It presents new business opportunities generated by digital convergence, and raises governance issues in digital convergence"--Provided by publisher.